(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Uterine primitive neuroectodermal tumors (PNETs) are a rare group of embryonal tumors, with less than 100 cases reported, mostly in postmenopausal women. Their rarity poses diagnostic and management challenges, contributing to high mortality. Case presentation: A 13-year-old presented with a 2-month history of abdominal pain, swelling, and heavy menstruation. Physical examination revealed a firm, fixed, nontender pelvic mass. She underwent a panhysterectomy and nodal resection. Histopathology confirmed PNET. The tumor recurred within a month, and intraoperative spillage occurred during repeat surgery. She developed obstructive uropathy and succumbed approximately 11 months after initial presentation. Conclusion: Uterine PNETs are aggressive tumors that rapidly infiltrate and obstruct pelvic structures. Owing to their rarity, diagnosis and management remain challenging, with high mortality. Keywords: embryonal tumors, obstructive uropathy, primitive neuroectodermal tumor, uterus